2021
DOI: 10.1080/09637486.2021.1900078
|View full text |Cite
|
Sign up to set email alerts
|

The use ofLactobacillus plantarumesterase genes: a biotechnological strategy to increase the bioavailability of dietary phenolic compounds in lactic acid bacteria

Abstract: In Lactobacillus plantarum the metabolism of hydroxybenzoic and hydroxycinnamic acid derivatives follows a similar two-step pathway, an esterase action followed by a decarboxylation. The L. plantarum esterase genes involved in these reactions have been cloned into pNZ8048 or pT1NX plasmids and transformed into technologically relevant lactic acid bacteria. None of the strains assayed can hydrolyse methyl gallate, a hydroxybenzoic ester. The presence of the L. plantarum tannase encoding genes (tanA Lp or tanB L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Most studies rely on quantification of a decrease in concentration of specific compounds with corresponding increase in expected metabolites. Many strains, however, encode for multiple esterases or glycosyl hydrolases with complementary or overlapping substrate specificities ( Gaur, 2022 ; Landete et al, 2021 ; Theilmann et al, 2017 ), which makes the unambiguous assignment of genotype to phenotype challenging or impossible. Only few studies used isogenic mutants to confirm the activity of specific enzymes in food fermentations ( Gaur, 2022 ; Gaur et al, 2023 ) and data on the expression of genes in complex food substrates remains scarce.…”
Section: Transformation Of Phenolic Compounds In Food Fermentationsmentioning
confidence: 99%
“…Most studies rely on quantification of a decrease in concentration of specific compounds with corresponding increase in expected metabolites. Many strains, however, encode for multiple esterases or glycosyl hydrolases with complementary or overlapping substrate specificities ( Gaur, 2022 ; Landete et al, 2021 ; Theilmann et al, 2017 ), which makes the unambiguous assignment of genotype to phenotype challenging or impossible. Only few studies used isogenic mutants to confirm the activity of specific enzymes in food fermentations ( Gaur, 2022 ; Gaur et al, 2023 ) and data on the expression of genes in complex food substrates remains scarce.…”
Section: Transformation Of Phenolic Compounds In Food Fermentationsmentioning
confidence: 99%
“…plantarum , gallate decarboxylase may be involved in the decarboxylation of both gallic acid and protocatechuic acid, and tannase (a specific class of esterase) may also exert this function [ 70 ]. Actually, it was demonstrated that the sequential action of esterase and decarboxylases drives the proper degradation of hydroxybenzoic (tannase/gallate decarboxylase) and hydroxycinnamic (esterase/phenolic acid decarboxylase) acids [ 18 ]. Tannase was investigated in several strains of Lpb .…”
Section: Resultsmentioning
confidence: 99%
“…plantarum strains and, to a lesser extent, in Lpb. pentosus [ 14 , 15 , 16 , 17 , 18 ], although this species is frequently isolated and associated with olives and their derived products [ 5 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also caffeic acid, vanillic acid and vanillin were mentioned as phenolic acids with antifungal activity (Elansary et al, 2019; Fitzgerald et al, 2005; Li et al, 2022). The presence of hydroxycinnamic acids, p-coumaric, caffeic acid and ferulic acid is correlated to the capacity of L. plantarum to metabolize these phenolic compounds (Landete et al, 2021) while the lower level of acetophenone in CFSs, compared to the control samples, was probably correlated to the reduced potential of LABs to produce chiral alcohols (Baydş et al, 2020). Interestingly, all CFSs produced decanal, a compound of the aldehyde class.…”
Section: Discussionmentioning
confidence: 99%